Bottom-up modeling approach and mesoscopic simulations in traffic system dynamics models. (March 2020) - Bureš, V; Režný, L; Zanker, M
The application of system dynamics modeling in various domains enables its continuous development and improvement. Transportation systems are associated with a necessity to tame their complexity. Despite its potential, system dynamics as a specific methodological and modeling approach is implemented only occasionally and application to road transportation systems is sporadic. Existing studies focus mostly on a macroscopic level of modeling. Thus, this study demonstrates how system dynamics can develop and simulate models at the meso level. It is based on an unconventional bottom-up modeling approach grounded in the modeling of T-shaped, X-shaped, and roundabout crossroads as fundamental building blocks. Model modularity enables its extension to any type of road network with the required structure or complexity. Model applicability is verified by testing on a case study in real-life settings. Modeling issues associated with this modeling approach and application domain are explained and possible solutions proposed. By developing a bottom-up approach and mesoscopic simulations, this study brings uniqueness and a certain level of novelty into the realm of system dynamics and traffic transportation modeling and simulation.